Redefining the phylogenetic relationships of European Angelica (Apiaceae) species - González-Toral, C; Estandía, A; Pérez, M; Holloway, TE; Nava, HS; Fernández Prieto, JA; Cires, E (Taylor & Francis, 2024)
Angelica (Apiaceae) is a large complex genus with high morphological diversity. The many taxonomic treatments explain the controversy regarding the number of European species, which range from four to ten. Molecular methods have unraveled the complicated Asian and American taxonomies; however, no comprehensive molecular study has been conducted on the European taxa. We aim to determine the number of different European Angelica s.l. taxa and their relationship within the Selineae tribe by conducting Maximum Likelihood (ML) and Bayesian Inference (BI) analyses based on the nuclear Internal Transcribed Spacer (ITS) and haplotype networks by Templeton Crandall and Sing and neighbour-net analyses based on the plastid trnL. Three separate Iberian species (A. angelicastrum, A. razulii and A. pyrenaea) form the new Iberian Angelica clade, which is sister to the Archangelica clade. Although morphologically different, A. pachycarpa cannot be differentiated from A. angelicastrum by molecular methods, casting new doubts on the existing taxonomies. Molecular evidences suggest that A. heterocarpa should be considered an estuary forma of A. sylvestris. The east and west A. sylvestris subclades support the subspecies A. sylvestris subsp. elatior and A. sylvestris subsp. villosa (including A. heterocarpa). Our evidences support the classification of A. palustris as Ostericum palustre.